Evaluation of cross‐reactivity between casein components using inhibition assay and in silico analysis. Issue 3 (19th November 2020) - Naito, Michihiro; Matsui, Teruaki; Yamada, Chikako; Tagami, Kazunori; Ito, Komei; Izumi, Hidehiko
Abstract: Background: We previously reported that the specific IgE levels to αs1‐casein (CN) and β‐CN in patients with cow's milk allergy decreased with similar dynamics during oral immunotherapy. Therefore, we hypothesized that αs1‐ and β‐CN have strong cross‐reactivity among CN components, despite the low similarity in the full‐length amino acid sequences. Methods: The αs1‐, β‐, and κ‐CN were purified from commercial cow's milk. We recruited 39 patients with cow's milk allergy, and the serum IgE levels for each CN component were measured by enzyme‐linked immunosorbent assay (ELISA). Cross‐reactivity between CN components was investigated by competitive ELISA against αs1‐CN. Sequence homology between CN components at the peptide level was calculated using in silico analysis and quantified by the property distance ( PD ) value. Results: The αs1‐CN–specific IgE levels exhibited a strong positive correlation with the β‐CN–specific IgE ( r = 0.945, P < .001). Complete competition was observed by β‐CN against αs1‐CN, suggesting the presence of common epitopes between them. In silico analysis detected 24 peptide sets with PD values lower than 10 between αs1‐ and β‐CN, and 14 sets between αs1‐ and κ‐CN. The amino acid sequences of αs1‐CN (E61‐E70) and β‐CN (I12‐E21) that showed the lowest PD value (5.30) were present in the characteristic sequence known as casein phosphopeptide (CPP). Conclusion: We detected strong cross‐reactivity between CN components. Furthermore, we found highly homologous sequences in the CPP region, which contains a core sequence of "SSSEE" with phosphorylated serine residues. Abstract :